2022
DOI: 10.37811/cl_rcm.v6i6.4140
|View full text |Cite
|
Sign up to set email alerts
|

Estrés Académico y su relación con la Resiliencia en Adolescentes

Abstract: El estrés académico es conocido como un aumento de la tensión en los estudiantes debido a diferentes factores presentes al momento del aprendizaje, causando daños en la salud mental de los mismos. Por otro lado, la resiliencia es la capacidad de afrontamiento de dificultades que posee la persona la cual podría tener relación con el estrés académico. Siendo el objetivo del presente estudio determinar si existe una relación entre estas variables en adolescentes. Para lo cual, se contó con 120 estudiantes adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
3
1
0
Order By: Relevance
“…In addition, the transition from preschool education to primary education involves the incorporation of situations that generally generate stress for all students, such as the incorporation of exams, changes in teachers and methodologies, a greater number of teachers, or homework to do at home. These results agree with previous studies [38,39,41], which lead us to support the idea that transitions between educational stages and adaptation to them are moments that generate greater stress for students. On the other hand, with respect to the sex of the children, no differences were found in the level of stress perceived by boys and girls, although the mean for girls was higher.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, the transition from preschool education to primary education involves the incorporation of situations that generally generate stress for all students, such as the incorporation of exams, changes in teachers and methodologies, a greater number of teachers, or homework to do at home. These results agree with previous studies [38,39,41], which lead us to support the idea that transitions between educational stages and adaptation to them are moments that generate greater stress for students. On the other hand, with respect to the sex of the children, no differences were found in the level of stress perceived by boys and girls, although the mean for girls was higher.…”
Section: Discussionsupporting
confidence: 93%
“…The correlational analysis raised in this study confirmed this negative association. Furthermore, significant negative correlations were obtained with both general and individual and contextual resilient factors, coinciding with previous studies [5,38,[57][58][59].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations